2011
DOI: 10.1177/0194599811403119
|View full text |Cite
|
Sign up to set email alerts
|

Adenoidectomy Technique in the United Kingdom and Postoperative Hemorrhage

Abstract: Use of suction diathermy in adenoidectomy appears to have a similar safety profile to conventional techniques and may offer additional benefits over traditional adenoid curettage. Further clinical and laboratory-based research into the complex interaction between diathermy usage and both adenoid and tonsillar tissue is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 12 publications
1
18
1
Order By: Relevance
“…SUCTION DIATHERMY ADENOIDECTOMY diathermy adenoidectomy was found to be 0.07 per cent. 13 These findings indicate that the post-operative haemorrhage rate of 1.6 per cent found in the current study is well within reported outcomes. It is interesting that suction diathermy adenoidectomy compares favourably with curettage adenoidectomy in the literature, in contrast to the comparisons between diathermy tonsillectomy and cold steel techniques.…”
Section: Discussionsupporting
confidence: 88%
“…SUCTION DIATHERMY ADENOIDECTOMY diathermy adenoidectomy was found to be 0.07 per cent. 13 These findings indicate that the post-operative haemorrhage rate of 1.6 per cent found in the current study is well within reported outcomes. It is interesting that suction diathermy adenoidectomy compares favourably with curettage adenoidectomy in the literature, in contrast to the comparisons between diathermy tonsillectomy and cold steel techniques.…”
Section: Discussionsupporting
confidence: 88%
“…The haemorrhage rate in our study was 4.23%, which is higher than rates presented by Gendy et al (2) and Lowe et al (3) (3.6% and 3.3%, respectively). Harju et al (4) and Ali et al (5) presented higher post-tonsillectomy haemorrhage rates (12% and 6.7%, respectively).…”
Section: Discussioncontrasting
confidence: 72%
“…On the other hand, there are studies which presented higher haemorrhage rates after using the cold dissection. Thirdly, there are studies that showed no effect of surgical technique on the haemorrhage rate (3-14). …”
Section: Introductionmentioning
confidence: 99%
“…A study on risk of postoperative hemorrhage showed that the data failed to demonstrate diathermy as a risk factor for hemorrhage following adenoidectomy despite a known interaction between diathermy and hemorrhage in tonsillectomy. [62] Operation time was found to be shorter than the conventional curette technique. No evidence of nasopharyngeal stenosis and scarring was seen in the majority of studies with suction electrocautery technique.…”
Section: Adenoidectomy Indicationsmentioning
confidence: 85%